The safety culture of the Ljubljana community health centre's employees - Tevžič Špela; Poplas-Susič Antonija; Klemenc-Ketiš Zalika (Sciendo, 2021)
Patient safety is one of the key aspects of healthcare quality and a serious global public health concern. Patient safety culture is a part of the patient safety concept. In Slovenia, primary care is easily accessible, and for medical care, it serves as a gatekeeper to hospital care. For several years, the quality and safety at the primary healthcare level have been the focus of several studies. The present study aimed to assess patient safety culture among all employees of the Community Health Centre Ljubljana.